2001
DOI: 10.1111/j.1469-7793.2001.0593c.xd
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic hypoxia on interstitial and blood adenosine, AMP, ADP and ATP in dog skeletal muscle

Abstract: 1. We investigated the effect of moderate systemic hypoxia on the arterial, venous and interstital concentration of adenosine and adenine nucleotides in the neurally and vascularly isolated, constant-flow perfused gracilis muscles of anaesthetized dogs.2. Systemic hypoxia reduced arterial P O 2 from 129 to 28 mmHg, venous P O 2 from 63 to 23 mmHg, arterial pH from 7.43 to 7.36 and venous pH from 7.38 to 7.32. Neither arterial nor venous P CO 2 were changed. Arterial perfusion pressure remained at 109 ± 8 mmHg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 35 publications
3
87
0
Order By: Relevance
“…However, Mo and Ballard (24) have shown that interstitial concentrations of Ado increased when sufficient Ado was infused arterially into dog skeletal muscle. The Ado infusion doses used in this study are likely large enough to account for much of the vasodilator response we observed during the Ado infusion trials, because the resting interstitial concentration of Ado in human skeletal muscle is very low (20).…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…However, Mo and Ballard (24) have shown that interstitial concentrations of Ado increased when sufficient Ado was infused arterially into dog skeletal muscle. The Ado infusion doses used in this study are likely large enough to account for much of the vasodilator response we observed during the Ado infusion trials, because the resting interstitial concentration of Ado in human skeletal muscle is very low (20).…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…This observation is in contrast to observations in the isolated dog limb 22 but in agreement with the observation that the endothelium is an effective barrier for adenosine. 23 Furthermore, plasma ATP increases during exercise, 31 but adenosine does not play a role in ATP-induced vasodilation, 25,29 and the breakdown products of ATP are, therefore, likely to be rapidly taken up by erythrocytes. 32 A methodological limitation may be that the rapid uptake and degradation of adenosine require sampling from veins closer to the active muscle.…”
Section: Arterial and Venous Plasma Adenosine Concentrations During Ementioning
confidence: 99%
“…In vitro evidence from studies on laboratory animals suggests that adenosine is increased in the venous efflux of contracting muscle, 21,22 as well as during hypoxia and ischemia. 23 However, because of rapid uptake by red blood cells, as well as degradation in plasma, the half-life of adenosine is estimated to be Ͻ1 second. 24 Therefore, despite the use of stop solutions and rapid centrifugation, adenosine determinations from blood samples are difficult to interpret, and the actual adenosine concentrations in the vascular beds supplying and draining resting and contracting muscles in humans remain unclear.…”
mentioning
confidence: 99%
“…Adenosine can be released from various types of cells. Recent studies suggest that aden- osine can be formed intracellularly by vascular endothelium or blood cells during systemic hypoxia (18) and also by interstitial cells during muscle contractions (10). However, it is unlikely that venular endothelium is a source of adenosine during resting conditions, because resting arteriolar diameter was unaffected by disruption of the venular endothelium (27), indicating that mediators released directly from venular endothelium may not be involved in regulation of arteriolar diameter under resting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase metabolites play a major role in venule-mediated arteriolar dilation in functional hyperemia, but possibly not in resting conditions (7). Adenosine is a potent vasodilator in many vascular beds, and adenosine release is increased during hypoxia, ischemia, or metabolic stress, when O 2 delivery is inadequate to meet the tissue demand (18,32). Adenosine exogenously infused through venules has been shown to vasodilate paired arterioles (11).…”
mentioning
confidence: 99%